2022
DOI: 10.3390/nano12101754
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Doped Graphitic Carbon Nitride Nanomaterials for Photocatalytic Environmental Applications—A Review

Abstract: In the current world situation, population and industrial growth have become major problems for energy and environmental concerns. Extremely noxious pollutants such as heavy metal ions, dyes, antibiotics, phenols, and pesticides in water are the main causes behind deprived water quality leading to inadequate access to clean water. In this connection, graphite carbon nitride (GCN or g-C3N4) a nonmetallic polymeric material has been utilized extensively as a visible-light-responsive photocatalyst for a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…There are many advantages of metal element doping of g-C 3 N 4 , firstly, metal doping in pure g-C 3 N 4 can interact with cations to generate lone electron pairs, which strengthens the electron trapping ability. [56] Moreover, metal-doping can regulate the (2 h) [76] morphology and crystalline phase of g-C 3 N 4 effectively, thereby enhancing the photocatalytic efficiency of the catalyst by building a non-homogeneous structure. Zhao et al introduced various ratios of cadmium into porous g-C 3 N 4 photocatalysts with higher electrical conductance, superior light absorption properties and photogenerated e + -h À pair migration efficiency, which significantly strengthened their photocatalytic activity.…”
Section: Degradation Of Tetracycline By Metal-doping G-c 3 Nmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many advantages of metal element doping of g-C 3 N 4 , firstly, metal doping in pure g-C 3 N 4 can interact with cations to generate lone electron pairs, which strengthens the electron trapping ability. [56] Moreover, metal-doping can regulate the (2 h) [76] morphology and crystalline phase of g-C 3 N 4 effectively, thereby enhancing the photocatalytic efficiency of the catalyst by building a non-homogeneous structure. Zhao et al introduced various ratios of cadmium into porous g-C 3 N 4 photocatalysts with higher electrical conductance, superior light absorption properties and photogenerated e + -h À pair migration efficiency, which significantly strengthened their photocatalytic activity.…”
Section: Degradation Of Tetracycline By Metal-doping G-c 3 Nmentioning
confidence: 99%
“…Introducing metal elements into g‐C 3 N 4 skeleton can effectively improve transfer and separation of charges, which is a tactic to improve photo‐catalytic performance [56] . Zong et al.…”
Section: Classification Of Doping G‐c3n4mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, various existing researches have proven that implanting the anion–cation into the g-C 3 N 4 frameworks could regulate their bandgap structure for broader visible-light absorption, facilitate the bulk phase and interface charge separation and lead to enhanced photocatalytic activity for H 2 evolution [ 21 , 22 , 23 ]. For instance, Qiao et al [ 24 ] found that a new intermediate energy level was formed in the bandgap of g-C 3 N 4 via the insertion of P into its skeleton, which received the electrons generated by light excitation from VB and thus improved the separation of photocarriers.…”
Section: Introductionmentioning
confidence: 99%